Study of Ce0.9Tb0.05Ln0.05O1.975 compounds as ceramic pigments - Šulcová P.; Vitásková L.; Trojan M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
New inorganic pigments based on CeO2 were synthesized as high-temperature Environment friendly inorganic pigments. This work is focused on mixed oxides based on ceria which are doped by rare earth elements, i.e. compounds with formula Ce0.9Tb0.05Ln0.05O1.975, where Ln means lanthanides. The pigments were prepared by the solid state reaction. Their colour properties were investigated depending on content of selected lanthanides and calcination temperature. All prepared pigments were applied into organic matrix and ceramic glaze. The pigments were evaluated from the standpoint of their structure, colour properties and particle sizes.